Stylistic Analysis of Surah Al-Zalzalah - Abdul Ghofur; Nur Huda; Ali Ja'far (Jurnal Alsinatuna, 2021)
This study aims to describe the various kinds of language styles in surah al-Zalzalah. This research is classified as a qualitative research and it uses descriptive methods by describing as well as analyzing the data in surah al-Zalzalah. Meanwhile, it applied stylistic approach which aims to explore the characteristics of the text based on the language style used in surah al-Zalzalah. In addition, the stylistic approach is used to obtain hidden meanings in surah al-Zalzalah so that the minor and major themes of the surah are revealed. This research confirms the existence of rhetorical language in various forms of language style spread in surah al-Zalzalah which are able to have greater influence and effect on the hearts and minds of the readers. From this research, it is concluded that there are twelve language styles in surah al-Zalzalah that are grouped into three stylistic levels. Among those twelve styles, three language styles are at the phonological level (al-mustawā al-sawti), four language styles are at the syntactic level, and five language styles are at the imagery level (al-mustawā al-taṣwīri).